THU0127 Pharmacodynamics of A Novel JAK1 Selective Inhibitor in Rat Arthritis and Anemia Models and in Healthy Human Subjects. (10th June 2014) - Voss, J.; Graff, C.; Schwartz, A.; Hyland, D.; Argiriadi, M.; Camp, H.; Dowding, L.; Friedman, M.; Frank, K.; George, J.; Goedken, E.; Lo Schiavo, G.; et al.
Abstract : Background: Anti-cytokine therapies have become the mainstay of treatment for rheumatoid arthritis (RA) disease symptoms and can arrest disease progression. Despite numerous treatment options there are still many RA patients who fail to experience substantial decreases in disease activity. Recently, Jak kinase blockade was shown clinically to be effective in managing disease and in some cases achieving remission. However, these first generation Jak inhibitors have failed to meet expectations due to dose-limiting tolerability and safety issues. ABT-494 is a second generation Jak kinase inhibitor with high selectivity for Jak1 thereby minimizing the potential for side effects related to Jak2 and Jak3 inhibition. Here we describe preclinical and early clinical data that suggest ABT-494 has potential to address some of the current unmet medical needs of RA patients. Methods: ABT-494 was engineered for increased selectivity for Jak1 using structural predictions that indicated the potential for differential binding interactions outside the ATP-binding active site of Jak1 but not Jak2. The efficacy and selectivity of ABT-494 were tested in a battery of relevant cellular and in vivo pharmacology assays including bone marrow colony formation, adjuvant induced arthritis (AIA), erythropoietin induced reticulocyte deployment and NK/NKT cell suppression. The potency of ABT-494 in a variety of complementary pharmacodynamic assays was also assessed at multiple dosages in healthy human subjects administered orally for 14 days. Results: ABT-494 demonstrates approximately 74 fold selectivity for Jak1 over Jak2 in cellular assays dependent on specific, relevant cytokines. ABT-494 is a potent inhibitor of inflammation and bone loss in rat AIA and, compared to Tofacitinib, spares relevant essential physiological processes such as erythropoietin signaling and peripheral NK cell counts at similarly efficacious doses in rats. When dosed orally for 14 days in healthy human subjects ABT-494 did not decrease reticulocyte or NK cell counts at predicted efficacious doses consistent with its pharmacodynamic properties in rats. Conclusions: ABT-494 is a Jak1-selective inhibitor that demonstrates efficacy in rat arthritis models. Preliminary evidence suggests that pharmacodynamic properties of ABT-494 are consistent between those observed in rodent models and in healthy human subjects. Taken together, these encouraging observations support further testing of ABT-494 in RA patients in Phase II randomized placebo controlled trials and indicate it may have increased potential to address patient needs over existing agents. Disclosure of Interest: : J. Voss Employee of: AbbVie, C. Graff Employee of: AbbVie, A. Schwartz Employee of: AbbVie, D. Hyland Employee of: AbbVie, M. Argiriadi Employee of: AbbVie, H. Camp Employee of: AbbVie, L. Dowding Employee of: AbbVie, M. Friedman Employee of: AbbVie, K. Frank Employee of: AbbVie, J. George Employee of: AbbVie, E. Goedken Employee of: AbbVie, G. Lo Schiavo: None declared, M. Morytko Employee of: AbbVie, R. O'Brien Employee of: AbbVie, R. Padley Employee of: AbbVie, M. Rozema Employee of: AbbVie, M. Rosebraugh Employee of: AbbVie, K. Stewart Employee of: AbbVie, G. Wallace Employee of: AbbVie, N. Wishart Employee of: AbbVie, A. Murtaza Employee of: AbbVie, L. Olson Employee of: AbbVie DOI: 10.1136/annrheumdis-2014-eular.3823